2021
DOI: 10.1007/s15010-020-01573-7
|View full text |Cite
|
Sign up to set email alerts
|

Torque Teno Virus plasma level as novel biomarker of retained immunocompetence in HIV-infected patients

Abstract: Purpose To predict the course of immune recovery (IR) in HIV-1-infected patients after initiation of combined antiretroviral therapy (cART) by determination of the plasma concentration of Torque Teno Virus (TTV). TTV has been identified as marker for risk assessment in immunosuppressed patients after transplantation procedures. Here, TTV was analyzed in HIV-1-infected therapy-naïve patients to evaluate its use as predictor of the course of IR for guidance of individualized treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 46 publications
1
14
1
Order By: Relevance
“…These fluctuations in the TTV level strongly suggest that analysis of the salivary TTV level is a sensitive biomarker for CD4+ status and HIV production in HIVpositive individuals currently undergoing ART. Our findings are consistent with earlier studies that demonstrated an association between the extent of TTV viremia in the systemic circulation and immune dysfunction in HIV-positive individuals (12,13,(20)(21)(22). The analysis of TTV titers in bone marrow and spleen tissues also confirmed that elevations in TTV parallel AIDS progression (22).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These fluctuations in the TTV level strongly suggest that analysis of the salivary TTV level is a sensitive biomarker for CD4+ status and HIV production in HIVpositive individuals currently undergoing ART. Our findings are consistent with earlier studies that demonstrated an association between the extent of TTV viremia in the systemic circulation and immune dysfunction in HIV-positive individuals (12,13,(20)(21)(22). The analysis of TTV titers in bone marrow and spleen tissues also confirmed that elevations in TTV parallel AIDS progression (22).…”
Section: Discussionsupporting
confidence: 92%
“…Our observation of elevated salivary TTV levels in HIVpositive subjects with AIDS-KS as compared to asymptomatic HIV-positive individuals is also consistent with this association. Investigations of the rate of TTV detection in blood from HIV-positive individuals have varied from <50% to >90% (13,20,21,23). This discordance is likely due in large part to the choice of primers utilized for TTV detection (11,13,24,25).…”
Section: Discussionmentioning
confidence: 99%
“…TTV, a highly prevalent and non-pathogenic small nonenveloped DNA virus, is an emerging marker to monitor immunosuppression in recipients of solid organ transplantations ( 17 , 20 ) and in patients with rheumatologic disease ( 21 ). Moreover, TTV is associated with immunocompetence in patients with HIV ( 22 ) and with response to SARS-CoV-2 vaccination in immunocompromised patients ( 18 , 23 ). TTV copy numbers in our sample, independent of type of apheresis, were comparable to those in healthy population, suggesting a less immunocompromised cohort compared to mentioned reference cohorts.…”
Section: Discussionmentioning
confidence: 99%
“… 70 , 71 In patients infected with HIV, TTV load was predictive for the course of immune recovery. 72 Recently, an association has been shown between TTV load and response to severe acute respiratory syndrome coronavirus type 2 vaccination in KTX recipients. 73 According to these findings, the central hypothesis of immune monitoring using TTV in SOT has formed: if the immune system is strong, the TTV load is low; this indicates a risk for organ rejection.…”
Section: Ttv—an Introductionmentioning
confidence: 99%